2008
DOI: 10.1016/j.yexcr.2007.10.031
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase η reduces the γ-H2AX response to psoralen interstrand crosslinks in human cells

Abstract: DNA interstrand crosslinks are processed by multiple mechanisms whose relationships to each other are unclear. Xeroderma pigmentosum-variant (XP-V) cells lacking DNA polymerase η are sensitive to psoralen photoadducts created under conditions favoring crosslink formation, suggesting a role for translesion synthesis in crosslink repair. Because crosslinks can lead to double strand breaks, we monitored phosphorylated H2AX (γ-H2AX), which is typically generated near double-strand breaks but also in response to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…For example, XP-V cells are sensitive to cisplatin, suggesting that bypass of cisplatin lesions may depend on Pol (1). Combined NER-and Pol -mediated lesion bypass has also been suggested as the likely mechanism for repairing DNA interstrand cross-links formed by mitomycin C (46) and psoralen (32). In contrast, Pol does not appear to play a role in replication past endogenous lesions such as 8-oxoguanine (3) or abasic sites (2).…”
mentioning
confidence: 99%
“…For example, XP-V cells are sensitive to cisplatin, suggesting that bypass of cisplatin lesions may depend on Pol (1). Combined NER-and Pol -mediated lesion bypass has also been suggested as the likely mechanism for repairing DNA interstrand cross-links formed by mitomycin C (46) and psoralen (32). In contrast, Pol does not appear to play a role in replication past endogenous lesions such as 8-oxoguanine (3) or abasic sites (2).…”
mentioning
confidence: 99%
“…In these experiments, using xeroderma pigmentosum patient-derived XPV cells, partial requirement for PolH was observed (42). Moreover, XPV cells are hypersensitive to cisplatin (43,44), and PolH was associated with processing of psoralen-induced crosslinks (45).…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that photoactivated psoralen (PUVA) can induce p53, ␥H2AX, and cell-cycle arrest and apoptosis (Mogi et al, 2008;Viola et al, 2008). The precise mechanism by which psoralen lesions induce these responses is not known.…”
Section: Resultsmentioning
confidence: 99%
“…However, psoralen-induced ICLs have been shown to induce DNA damage responses such as phosphorylation of the histone variant H2AX (␥H2AX) throughout the cell cycle and induce an arrest at the G 1 /S border of the cell cycle (Mogi et al, 2008;Viola et al, 2008). We and others have shown that agents that block transcription induce p53 (Yamaizumi and Sugano, 1994;Ljungman and Zhang, 1996;Ljungman and Lane, 2004) and apoptosis in human cells (Ljungman and Zhang, 1996;McKay et al, 1998;Brash et al, 2001).…”
mentioning
confidence: 99%